Approximation for combinatorial network optimisation using Tsallis entropy. Issue 14 (1st July 2013) - Liao, Shengbin; Zhang, Qingfu
Abstract : Recent research shows that a combinatorial network optimisation problem can be approximated by adding a Shannon entropy term to its objective function. This Letter generalises it to the case of Tsallis entropy and provides the mathematical proof.